Implementation Of Coso-Based Pharmaceutical Inventory Stock-Taking At The Cinta Bunda Clinic - Muhammad Syahrudin; M. Galih Munggaran (Inaba of Community Services Journal, 2024)
To improve service delivery and reduce preventable deaths and illnesses, the government and the healthcare industry are endeavoring to expand the growing number of healthcare facilities in Indonesia. The transactions that occur can also cause stock mismatches in the bookkeeping with the physical ones in the clinic warehouse so that to prevent this it is necessary to do stock-taking. The STIE Gema Widya Bangsa Community Service Activity team after conducting an initial survey and talking to the clinic management about the problem. The implementation method in this Community Service Activity program is arranged systematically through several stages. The application of the inventory control system for medical and non-medical goods at the Cinta Bunda Clinic is expected to improve the quality of the inventory control system into a relevant and accurate inventory report.